A theranostic nrGO@MSN-ION nanocarrier developed to enhance the combination effect of sonodynamic therapy and ultrasound hyperthermia for treating tumor - Chen, Yu-Wei; Liu, Tse-Ying; Chang, Po-Hsueh; Hsu, Po-Hung; Liu, Hao-Li; Lin, Hong-Cheu; Chen, San-Yuan (My University, 2016)
Sonodynamic therapy (SDT), which induces activation of sonosensitizers in cancer cells through ultrasound irradiation, has emerged as an alternative and promising noninvasive therapeutic approach to kill both superficial and deep parts of tumors. In this study, mesoporous silica (MSN) grown on reduced graphene oxide nanosheet (nrGO) capped with Rose Bengal (RB)-PEG-conjugated iron-oxide nanoparticles (IONs), nrGO@MSN-ION-PEG-RB, was strategically designed to have targeted functionality and therapeutic efficacy under magnetic guiding and focused ultrasound (FUS) irradiation, respectively. The singlet oxygen produced by ultrasound-activated RB and the ultrasound-induced heating effect was enhanced by rGO and IONs, which improved the cytotoxic effect in cancer cells. In an animal experiment, we demonstrated that the combination of sonodynamic/hyperthermia therapy with magnetic guidance using this nanocomposite therapeutic agent can produce remarkable efficacious therapy in tumor growth inhibition. Furthermore, the combination effect induced by FUS irradiation produces significant damage to both superficial and deep parts of the targeted tumor.